IELTS Teachers and Test Takers’ Attitudes towards IELTS Writing Tasks - Rentauli Mariah Silalahi (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
This study is conducted to explore the attitudes of teachers actively involved in preparing student candidates to sit for an IELTS test and IELTS test takers who have experienced doing the test towards the usefulness of the IELTS writing exam in preparing candidates for university level studies in an English speaking country. It is also carried out in order to find out if the IELTS writing exams, task one and task two, meet the espoused goals of expressing critical thinking. Accordingly, a questionnaire was administered to 2 IELTS teachers and 16 IELTS test takers in an Indonesian private university, followed with an interview. The results indicated that both tasks of the IELTS writing test were perceived by the teachers and students as having positive effect on training the test takers to think critically and logically yet bearing a slight relationship with skills needed at faculty level because the writing assignments at university would be very much different in criteria of assessment and constraints for completion than those tested at IELTS test. However, both teachers and students mostly have positive attitudes towards the test as a reliable tool to assess their level of English proficiency. This study will mostly be very useful for teacher practitioners who have responsibilities in preparing students to sit for an IELTS test.